2016
DOI: 10.1111/een.12335
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of an aposematically coloured butterfly by wild birds in a tropical forest

Abstract: 1. Birds are considered to be the primary selective agents for warning colouration in butterflies, and select for aposematic mimicry by learning to avoid brightly coloured prey after unpleasant experiences. It has long been thought that bright colouration plays an important role in promoting the avoidance of distasteful prey by birds.2. The hypothesis that warning colouration facilitates memorability and promotes predator avoidance was tested by means of a field experiment using distasteful model butterflies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…The facsimiles were divided and set into 49 independent forest sites, each site containing three of each facsimile phenotype. We used a four-day predator exposure time period because previous work (Stobbe and Schafer 2008;Merrill et al 2012;Finkbeiner et al 2012Finkbeiner et al , 2014Seymoure and Aiello 2015;Dell'Aglio et al 2016) shows this to be enough time for local predators in a home range to come in contact with (and attack) artificial butterfly facsimiles. Facsimiles within the forest sites were placed at least 4 m apart and in alternating order, and attached onto leaves or branches in appropriate resting positions (see Fig.…”
Section: Preliminary Control Studymentioning
confidence: 99%
“…The facsimiles were divided and set into 49 independent forest sites, each site containing three of each facsimile phenotype. We used a four-day predator exposure time period because previous work (Stobbe and Schafer 2008;Merrill et al 2012;Finkbeiner et al 2012Finkbeiner et al , 2014Seymoure and Aiello 2015;Dell'Aglio et al 2016) shows this to be enough time for local predators in a home range to come in contact with (and attack) artificial butterfly facsimiles. Facsimiles within the forest sites were placed at least 4 m apart and in alternating order, and attached onto leaves or branches in appropriate resting positions (see Fig.…”
Section: Preliminary Control Studymentioning
confidence: 99%
“…Artificial prey experiments have become powerful tools for mimicry research in natural settings by allowing us to manipulate the signals that predators encounter and measure predators’ responses in the field. Significant advances using this method (especially for butterflies) include assessing the influence of roosting behavior on warning signals (Finkbeiner et al., 2012), studying the relative contributions of wing color versus pattern to predator deterrence (Finkbeiner et al., 2014), uncovering how eyespot size and number influence predation (Ho et al., 2016; Stevens, Hardman, & Stubbins, 2008), analyzing the evolution of novel colors in warning signals (Dell'Aglio et al., 2016; Finkbeiner, Fishman, et al., 2017; Wee & Monteiro, 2017), and dissecting the importance of white bands (false boundaries) and disruptive coloration for protection from predators (Seymoure & Aiello, 2015). Further experiments are needed that integrate phenotypic and behavioral qualities of Batesian mimics with predator psychology and that assess the importance of model frequency dependence in Batesian systems.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments allow for precise manipulation of artificial models in order to test specific hypotheses about how mimicry phenotypes, or parts thereof, may experience differential predation. The artificial prey method has been implemented in diverse butterfly systems to address the relationship between wing patterning and predation (Dell'Aglio, Stevens, & Jiggins, 2016; Finkbeiner, Briscoe, & Mullen, 2017; Finkbeiner, Briscoe, & Reed, 2012, 2014; Finkbeiner, Fishman, Osorio, & Briscoe, 2017; Ho, Schachat, Piel, & Monteiro, 2016; Merrill et al., 2012; Seymoure & Aiello, 2015; Wee & Monteiro, 2017). In this study, we applied the artificial prey method to study how female‐limited Batesian mimicry operates in wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, past empirical studies have shown that, a JND value of less than three (< 3) indicates that birds are unable to differentiate between two spectra under normal viewing conditions [47, 49]. As previous work [50] suggested a threshold value of ≤ 3, we also adopted it as the criteria for our study.…”
Section: Methodsmentioning
confidence: 99%